Conceptualisation and design of a protocol for a novel social drivers and primary care screening tool in paediatric orthopaedics: a quality improvement initiative - Devika A Shenoy; Kathryn Radulovacki; Christian Zirbes; Rachelle Shao; Giussepe Yanez; Anthony A Catanzano (BMJ Open Quality)
Introduction Paediatric patients with elevated healthcare needs have limited access to care, contributing to insufficient preventive services. Social drivers of health (SDOH), such as inadequate nutrition and poor community support, contribute substantially to paediatric health. In order to promote value-based healthcare, specialty providers like orthopaedic surgeons can serve as an entry point to connect patients to SDOH and primary care resources. The purpose of this short report is to provide a framework for other institutions for an ongoing screening programme.Overview of programme Informed on prior initiatives, we designed a systematic screening programme for SDOH, obesity (via body mass index (BMI)) and primary care access in a paediatric orthopaedics clinic, for English-speaking and Spanish-speaking patients <18 years old. We record age, sex, race/ethnicity, language, orthopaedic condition, Area Deprivation Index and Childhood Opportunity Index from the electronic record previsit. BMI ≥95th percentile triggers referral to a paediatric obesity management programme. An institutional SDOH screen detects financial, food, transportation, housing and utility needs. A positive screen triggers a referral to institution and state-specific resources. A five-question Primary Care Access Screen identifies gaps in primary care access. A positive screen triggers an internal referral to paediatric primary care. Patients are flagged before visits, and screening results are reviewed. Students place referrals for positive screens, finalised by providers. Follow-up occurs at 6 weeks.Data collection We assess screen positivity, referral uptake and completed appointments for all patients at 6 weeks.